Emergent Patterns of Switching Behaviors and Intercultural Communication Styles of Global Virtual Teams During Distributed Decision Making - Zakaria, Norhayati (Journal of international management, 2017)
The purpose of this study is to explain the distinctive patterns of intercultural communication styles exhibited during the distributed decision making process in global virtual teams (GVTs). The study applied Hall's (1976) high context vs. low context theoretical lens to a corpus of archival online messages (n=1600 emails) generated by the United Nation World Summit on Information Society (WSIS) Civil Society. By using email as a primary medium for global collaboration, the GVT comprising of Civil Society participants was engaged in decision-making processes among different teams. The goal is to bring multi-stakeholders together in developing policy on the roles and utility of information communication technology for development of the Information Society. Our findings show that culture and the cultural values to which team members subscribe do influence the way decisions are made and communicated in three distinct phases—problem identification, proposal making and solutions. In addition, the results found evidence of an interesting behavioral pattern we call “switching,” in which an individual's communication style changes depending on purpose, roles, situation, and people—another form of context-based mode of online communicative behavior. This evidence of switching behavior is crucial because it shows that intercultural communication styles are fluid rather than fixed.